Effects of waterlogging on ion translocation and biochemical responses in maize (Bangladesh Journal of Botany, 2025)
An experiment was conducted to investigate the impact of waterlogging onion transport and some biochemical parameters, including the concentration of reducing and total sugar, proline, protein and antioxidant enzymes in the root and shoot of maize plants grown in solution culture. Waterlogging suppressed the accumulation of K+, NO3-, Ca2+ and Mg2+ in maize plants. On the other hand, the waterlogged state dramatically increased the accumulation of Na+ and Fe2+ in different parts of the maize plants. Waterlogging stimulated the level of total and reducing sugars as well as proline in the root and shoot of maize plants. Activities of different antioxidant enzymes were found higher under waterlogged condition.Bangladesh J. Bot. 54(1): 91-98, 2025 (March)